Hubungan Karakteristik Ibu Dengan Perkembangan Anak Usia 1-5 Tahun Di Wilayah Kerja Puskesmas Mandai (Window of Public Health Journal, 2025)
The role of parents is important in optimizing a child's development. Parents must always provide stimulation to children The role of parents is important in optimizing a child's development. Parents must always provide stimulation to children in all aspects of development, both gross and fine motor skills, language, and social behavior. Development is a regular pattern related to changes in structure, thoughts, feelings, or behavior resulting from a dynamic process and continuity as life progresses marked by a series of increases, constant conditions, and decreases. An important period in children is toddlerhood. Child development has a critical period, namely the period of children under five years of age. In the first five years of life, the child's growth and development process runs very rapidly and optimally where children really need stimulation that is useful for their development. This is a period of rapid growth and development, where every moment counts. Growth and development are interrelated things that cannot be separated and occur simultaneously. The purpose of this study was to analyze the characteristics of mothers with the development of children aged 1-5 years in the Mandai Health Center work area in 2024. The method used was the cross-sectional approach method. The results of the study showed no relationship between maternal characteristics and the development of children aged 1-5 years in the Mandai Health Center work area. The conclusion of the study, there is no relationship between maternal characteristics and child development in the Mandai Health Center work area. Research suggestions, it is expected that parents, especially mothers, carry out various activities so that all the roles of mothers can be carried out in every aspect of child development stimulation. For Health Centers to add more information related to the importance of optimizing the role of mothers in stimulating child development in counseling activities and other health center programs.